AL amyloidosis - pathogenesis and prognosis are determined by the amyloidogenic potential of the light chain and the molecular characteristics of malignant plasma cells - Seckinger, Anja; Hegenbart, Ute; Beck, Susanne; Emde-Rajaratnam, Martina; Bochtler, Tilmann; Kimmich, Christoph; Müller-Tidow, Carsten; Jauch, Anna; Schönland, Stefan; Hose, Dirk (Blood, 2018)
INTRODUCTION. Systemic light chain amyloidosis (AL) is caused by accumulation of plasma cells producing misfolded monoclonal light chains depositing as amyloid fibrils in different organs, most frequently heart and kidney. AIM of our study is first assessing the molecular characteristics of malignant plasma cells from AL-patients in relation to those from MGUS, asymptomatic, and symptomatic myeloma: Are these plasma cells different, does this difference explain amyloidogenicity? Does AL correspond to a certain developmental stage during evolution of symptomatic myeloma? Secondly, to what extent is prognosis determined by amyloid-deposition (organotropism, amount, amyloidogenicity) vs. number and molecular characteristics of malignant plasma cells? PATIENTS & METHODS. Consecutive patients (n=3023) with AL (n=582), MGUS (n=306), asymptomatic (n=444, AMM), or previously untreated, therapy-requiring multiple myeloma (n=1691, MM) were included. CD138-purified plasma cell samples were subjected to iFISH (n=582/306/444/1691), 1297 to gene expression profiling using Affymetrix U133 2.0 plus arrays (n=196/64/272/765), 712 to RNA- (n=124/52/38/489), and 258 to whole exome sequencing (n=115/53/39/51). Samples of normal bone marrow plasma cells, memory B-cells, and polyclonal plasmablasts were used as comparators. The CoMMpass-cohort (n=647) was used as comparator for the mutational spectrum of myeloma. RESULTS. Prognosis. By AL-factors. Expectedly, organ involvement, i.e. heart only vs. kidney only vs. heart+kidney vs. other (overall survival (OS), P=.001), the amount of free light chains (dFLC ≥18 mg/dL, HR=2.56, P=.01), and the cardiac European Mayo IIIB score (I/II/IIIA/IIIB, median OS 110/55/16/3 months, HR=1/1.94/3.73/7.90, P<.001) strongly determine prognosis (Fig. 1A). By malignant plasma cell factors. High proliferation rate (HR=3.58, P=.001) and expression-based risk factors for MM (GEP70 high, HR=2.38, P=.005; Rs-score high HR=4.63, P<.001) identify patients with very adverse prognosis (Fig. 1A). Tumor load, e.g. plasma cell infiltration >10%/>30% (HR=1.31/1.81, P=.01, P=.002) and M-protein ≥ 30g/l (HR=3.01, P=.005), are likewise prognostic (Fig. 1A). In multivariate analysis, all tested AL-specific (European Mayo IIIB score) and malignant plasma cell factors (proliferation or GEP70 and plasma cell infiltration) are independent. Molecular characteristics. iFISH. As MM (96.2%) and AMM (92.8%) AL-patients (93.1%) carry at least one recurrent myeloma typical aberration. The mean number of progression-associated aberrations in AL (n=0.98) fits between MGUS (n=0.85) and AMM (n=1.45) with significant difference compared to AMM (P<.001) unlike to MGUS. Main differences in frequency are found for t(11;14) and hyperdiploidy with a comparable pattern of non-etiologic aberrations. Gene expression (GEP and RNA-seq). Aberrant plasma cells in AL amyloidosis show the least difference with AMM, followed by MGUS and MM. In principal component analysis, AL overlaps with AMM and MGUS, independent of presence or absence of heart involvement (Fig. 1B). Pairwise assessment of similarity using a multivariate generalization of the squared Pearson correlation coefficient shows closest similarity to AMM and MM followed by MGUS, with comparable differences to normal plasma cells, polyclonal plasmablasts, and memory B-cells. Significantly more AL-patients present with higher proliferation rate vs MGUS (P<.001) and AMM (P<.02). AL and MM differ significantly regarding distinct molecular entities as determined by GEP (e.g. TC-classification; Fig. 1C). Mutation spectrum in AL amyloidosis vs. MM. From the 20 most frequently synonymously mutated non-Ig transcripts (CoMMpass-cohort), 16 could likewise be detected in AL amyloidosis, i.e. KRAS, NRAS, IGLL5, DIS3, FAM46C, MUC16, BRAF, TRAF3, PCLO, RYR2, FATA4, CSMD3, TP53, DNAH5, RYR2A, and FLG. CCND1 mutations were significantly more frequent in AL and AMM compared to MM (P=.02). DISCUSSION & CONCLUSION. Pathogenesis and prognosis of AL amyloidosis are explained both by AL-specific and malignant plasma cell characteristics. Aberrant plasma cells in AL amyloidosis show the same aberration- and expression pattern and a “molecular age” between MGUS and AMM, most closely resembling the latter. AL amyloidosis is thus mostly a rather early plasma cell dyscrasia with an unstable and toxic immunoglobulin light chain. - Disclosures - Seckinger: Celgene: Research Funding; EngMab: Research Funding; Sanofi: Research Funding. Hose: Celgene: Honoraria, Research Funding; Sanofi: Research Funding; EngMab: Research Funding.